2018
DOI: 10.1016/j.dadm.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E particle size is increased in Alzheimer's disease

Abstract: Introduction Apolipoprotein E4 (apoE4) is the predominant risk factor for late-onset Alzheimer's disease (AD), but the question of which structural differences might explain its effect remains unclear. Methods We compared high-density lipoprotein–like apoE particles from 12 AD and 10 control patients using size-exclusion chromatography. Results ApoE particles from patients genotyped as ε4/ε4 were 2.2 ± 0.3 times as massive as particles from ε… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
4
9
0
Order By: Relevance
“…Extracellular vesicles are typically 30-100 nm in diameter suggesting that the smaller structures (5-30 nm) are likely lipid particles (van Niel et al, 2018). These data are consistent with lipid particles secreted from neuronal cell lines (Nelson and Sen, 2018) and support the conclusion that neurons release lipoprotein-like particles. To better assess whether neurons can make lipid particles, we employed focused ion beam scanning electron microscopy (FIB-SEM) technology (Xu et al, 2017), on adult mouse hippocampal tissue prepared with imidazole-buffered osmium tetroxide to stain lipids such as LDs and lipoprotein particles (Zhang et al, 2011;Rong et al, 2015).…”
Section: Astrocytes Internalize Fas Secreted By Neurons In Lipoprotein Particlessupporting
confidence: 79%
“…Extracellular vesicles are typically 30-100 nm in diameter suggesting that the smaller structures (5-30 nm) are likely lipid particles (van Niel et al, 2018). These data are consistent with lipid particles secreted from neuronal cell lines (Nelson and Sen, 2018) and support the conclusion that neurons release lipoprotein-like particles. To better assess whether neurons can make lipid particles, we employed focused ion beam scanning electron microscopy (FIB-SEM) technology (Xu et al, 2017), on adult mouse hippocampal tissue prepared with imidazole-buffered osmium tetroxide to stain lipids such as LDs and lipoprotein particles (Zhang et al, 2011;Rong et al, 2015).…”
Section: Astrocytes Internalize Fas Secreted By Neurons In Lipoprotein Particlessupporting
confidence: 79%
“…A more recent study using iPSC-derived astrocytes showed that apoE4 is less lipidated than apoE3, potentially impacting apoE4 neurotrophic role ( Zhao J. et al, 2017 ). In the CSF of middle-aged adults (average age 54.5 years) with no dementia, apoE particles were smaller in both ε3/ε4 and ε4/ε4 individuals than in ε3/ε3 individuals, but larger in ε2/ε3 individuals ( Heinsinger et al, 2016 ; Nelson and Sen, 2019 ). The cholesterol efflux ability of individuals homozygous for APOE4 is reduced in CSF ( Yassine et al, 2016 ).…”
Section: Metabolism and Apoe Isoformsmentioning
confidence: 95%
“…Allelic variation of APOE will influence the lipid particle size that apoE binds to, the type of lipids and proteoglycans that apoE will interact with, the brain lipid profile, and apoE’s interacting abilities with its receptors. For instance, a study comparing apoE particle size from temporal lobe brain homogenates of AD and control patients by size-exclusion chromatography found that apoE particles in APOE4/4 patients were twice as big as those from APOE3/3 AD patients and APOE3/3 control subjects [ 125 ]. However, this study did not include genotype control APOE4/4 subjects, and no comparison was performed between APOE4/4 and APOE3/3 control subjects.…”
Section: Impact Of Apoe Isoforms On Receptor and Target Bindingmentioning
confidence: 99%